Sedimentology and facies analysis of the Ordovician San José and Sandia Formations in the Sandia region, Eastern Cordillera of southern Peru - Spiske, Michaela (2006)
The Ordovician sedimentary rocks of the San José Fonnation (Iparo and Purumpata members) and the Sandia Formation have been investigated in the regions of Sandia, Sina, Ollantaytambo and Calca which lie within the Peruvian Eastem Cordillera. The Iparo Member (upper Lower Ordovician to lower Middle Ordovician) consists of dark grey, hemipelagic mudstones with a rich graptolite fauna and was deposited in a low energy, deep marine envirom11ent. Pyrite rich and pyrite poor units were caused by temporal)' changes in oxygen content from anaerobic to dysoxic or oxic conditions. Low energy and probably distal turbidites are interbedded within the normal background sedimentation. The pelitic rocks of the Purumpata Member (Daniwilian) were deposited under more oxygenated but stilllow energetic conditions. The qumtz-sandstones, siltstones and mudstones ofthe Sandía Fonnation (upper Daniwilian to middle Upper Ordovician) represent a shallow marine, well oxygenated environment. Sedimentary structures and ichnofossils give evidence of storms that brought a high volume of sediment into the max. 1OOm deep sedimentary environment. Coarsening upward trends are connected toa stepwise relative drop in sea level. Syn-sedimentary tectonic movements during the Ordovician, and hence an increased sediment input are indicated by turbidites, slumps and a breccia.